Pemanfaatan Smartphone Dalam Pembelajaran Pendidikan Agama Islam Pada Era Pandemi Covid-19 Di Sekolah Menengah Pertama Muhammadiyah 4 Kebomas Gresik - Aisyia, Dewy Nasyiatul; Noor Amirudin; Man Arfa’ Ladamay (Jurnal Mahasiswa Pendidikan, 2022)
Smartphones are electronic devices that are developing quite rapidly in modern times like today, in the world of work smartphones have begun to be used to help work, while in the world of education smartphones are also used as media and learning resources especially during the covid-19 pandemic, where learning is carried out online so that there is a need for media to support learning including smartphone media as was done at SMP Muhammadiyah 4 Kebomas where smartphones are used as learning media for Islamic Religious Education in the Covid-19 pandemic era. This type of research is descriptive qualitative. The subjects of this thesis research are: Principal, Islamic Religious Education Teacher, Deputy Head of Student Affairs, Representatives of parents and students. This qualitative research method uses three data collection techniques, namely: a) Observation, b) Interview, and c) Documentation. The results showed that online learning with the use of smartphones at SMP Muhammadiyah 4 Kebomas has several obstacles and is considered less effective because not all students have learning media.